The Impact of Information Technology Utilization, Digital Literacy, and Competencies on the Performance of KPU Employees in Kepahiang Regency - Indriana Indriana; Suwarni Suwarni; Kresnawati Kresnawati (UNIVED Press, 2026)
The development of information technology in the Industry 5.0 era has accelerated digital transformation in the public sector, including election administration. The General Election Commission (KPU) utilizes various digital information systems to support effective, transparent, and accountable electoral processes. In this context, information technology, digital literacy, and employee competency are important factors influencing employee performance. This study employed a quantitative explanatory approach involving all employees and commissioners of the KPU of Kepahiang Regency. Data were collected through online questionnaires and analyzed using multiple linear regression. The results indicate that competency has the strongest influence on employee performance, while digital literacy has a positive and significant effect. Employees with strong digital literacy are better able to utilize applications, process information accurately, and adapt to digital work systems. In contrast, information technology does not significantly affect employee performance, suggesting that its utilization remains in an adaptive stage and requires optimization through improved implementation and continuous training. Simultaneously, information technology, digital literacy, and competency significantly influence employee performance, with an R² value of 0.898, indicating that 89.8% of employee performance is explained by these variables. In conclusion, information technology, digital literacy, and competency jointly contribute to employee performance. These findings highlight the importance of strengthening digital capabilities and competencies to support high-quality election administration.